2017
DOI: 10.1002/ejp.1086
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the modulation of nociception in mice by central mast cells

Abstract: Background Hyperalgesia that develops following nerve ligation corresponds temporally and in magnitude with the number of thalamic mast cells located contralateral to the ligature. We tested the possibility that mast cells modulate nociception centrally, similar to their role in the periphery. Methods We examined the central effect of two hyperalgesic compounds that also induce mast cell degranulation and stabilized mast cells using cromolyn. Results Thermal hyperalgesia (tail flick) induced by nerve growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
1
13
0
1
Order By: Relevance
“…Almost 50% of histamine and 25% of TNF‐α are attributed to mast cells in the rat brain . Mast cell activation may therefore contribute to nociception via direct central interactions in the brain as demonstrated recently in a spinal nerve ligation model in mice . This study also demonstrated that nerve growth factor (NGF), formalin, and dynorphin‐induced hyperalgesia involved degranulation of mast cells in the brain of mice.…”
Section: Mast Cells Interact With the Nervous Systemsupporting
confidence: 67%
See 3 more Smart Citations
“…Almost 50% of histamine and 25% of TNF‐α are attributed to mast cells in the rat brain . Mast cell activation may therefore contribute to nociception via direct central interactions in the brain as demonstrated recently in a spinal nerve ligation model in mice . This study also demonstrated that nerve growth factor (NGF), formalin, and dynorphin‐induced hyperalgesia involved degranulation of mast cells in the brain of mice.…”
Section: Mast Cells Interact With the Nervous Systemsupporting
confidence: 67%
“…26,53 Mast cell activation may therefore contribute to nociception via direct central interactions in the brain as demonstrated recently in a spinal nerve ligation model in mice. 44 This study also demonstrated that nerve growth factor (NGF), formalin, and dynorphin-induced hyperalgesia involved degranulation of mast cells in the brain of mice. It is likely that mast cells in the CNS are a critical player in the multicellular repertoire orchestrating central sensitization.…”
Section: Mast Cell's Role In Central Sensitization and Neuroinflammmentioning
confidence: 78%
See 2 more Smart Citations
“…Pain in fibromyalgia involves neuroinflammatory processes triggered by mast cells and microglia [31][32][33][34][35]. Mounting evidence indeed supports the role of mast cells in fibromyalgia comorbid disorders and painful conditions [6,36,37].…”
Section: Inflammatory Mediators and Innate Immunity In The Generationmentioning
confidence: 97%